Early phase clinical trials extension to guidelines for the content of statistical analysis plans. (7th February 2022) - Homer, Victoria; Yap, Christina; Bond, Simon; Holmes, Jane; Stocken, Deborah; Walker, Katrina; Robinson, Emily J; Wheeler, Graham; Brown, Sarah; Hinsley, Samantha; Schipper, Matthew; Weir, Christopher J; et al.
Abstract : This paper reports guidelines for the content of statistical analysis plans for early phase clinical trials, ensuring specification of the minimum reporting analysis requirements, by detailing extensions (11 new items) and modifications (25 items) to existing guidance after a review by various stakeholders.